Mutual connected IL-6, EGFR and LIN28/Let7-related mechanisms modulate PD-L1 and IGF upregulation in HNSCC using immunotherapy - Li, Junjun; Xiao, Yazhou; Yu, Huayue; Jin, Xia; Fan, Songqing; Liu, Wei (Frontiers in Oncology, 2023)
The development of techniques and immunotherapies are widely applied in cancer treatment due to checkpoint inhibitors, adoptive cell therapy, and cancer vaccines. Radiation therapy, surgery, and chemotherapy give enduring anti-tumor effects. Minority people utilize single-agent immunotherapy, and most people do not recover from the immunotherapy. The difficulties are resolved by including the biomarkers to choose the non-responders' and responders' potentials. In addition, chemotherapy, radiotherapy, and microbiota transplantation treat cancer patients. The possibility of the potential amplification and side effects are examined to improve cancer therapy. The Head and Neck Squamous Cell Carcinoma (HNSCC) is analyzed with the help of programmed cell death ligand 1 (PD-L1) and Insulin-like growth factor (IGF). But how IGF and PD-L1 upregulation depends on IL-6, EGFR, and LIN28/Let7-related mechanisms are poorly understood. Briefly, IL-6 stimulates gene expressions of IGF-1/2, and IL-6 cross-activates IGF-1R signaling, NF-κB, and STAT3. NF-κB, PD-L1 genes, and STAT3 genes to encourage their expressions. IL-6/JAK1 primes PD-L1 for STT3-mediated PD-L1 glycosylation stabilizes PD-L1 and trafficks it to the cell surface. Moreover, ΔNp63 is predominantly overexpressed over TAp63 in HNSCC, elevates circulating IGF-1 levels by repressing IGFBP3, and activates insulin receptor substrate 1 (IRS1).TP63 and SOX2 form a complex with CCAT1 to promote EGFR expression. EGFR activation through EGF binding extends STAT3 activation, and EGFR and its downstream signaling prolong PD-L1 mRNA half-life. PLC-γ1 binding to a cytoplasmic motif of elevated PD-L1 improves EGF-induced activation of inositol 1,4,5-tri-phosphate (IP3), and diacylglycerol (DAG) subsequently elevates RAC1-GTP. RAC1-GTP was convincingly demonstrated to induce the autocrine production and action of IL-6/IL-6R, forming a feedback loop for IGF and PD-L1 upregulation. Furthermore, the LIN28-Let7 axis mediates the NF-κB-IL-6-STAT3 amplification loop, activated LIN28-Let7 axis up-regulates RAS, AKT, IL-6, IGF-1/2, IGF-1R, Myc, and PD-L1, plays pivotal roles in IGF-1R activation and Myc, NF-κB, STAT3 concomitant activation. Therefore, based on a detailed mechanisms review, our article firstly reveals that IL-6, EGFR, and LIN28/Let7-related mechanisms mediate PD-L1 and IGF upregulation in HNSCC, which comprehensively influences immunity, inflammation, metabolism, and metastasis in the tumor microenvironment, and might be fundamental for overcoming therapy resistance.